2018
DOI: 10.3390/ma11050862
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Tunable Wavelength Selectivity of Metamaterials in Near-Field and Far-Field Radiative Thermal Transport

Abstract: Radiative thermal transport of metamaterials has begun to play a significant role in thermal science and has great engineering applications. When the key features of structures become comparable to the thermal wavelength at a particular temperature, a narrowband or wideband of wavelengths can be created or shifted in both the emission and reflection spectrum of nanoscale metamaterials. Due to the near-field effect, the phenomena of radiative wavelength selectivity become significant. These effects show strong … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 71 publications
0
17
0
Order By: Relevance
“…Datas and Martí [ 10 ] reviewed the state of the art and historical development of TPV for space application along with the main competing technologies. Tain et al [ 11 ] reported the recent progress of near-field and far-field radiative heat transfer, various design structures of metamaterials and their properties, and focused on the exploration of tunable radiative wavelength selectivity of nano-metamaterials. More recently, in 2019, Sakakibara et al [ 12 ] reviewed the state of the art of radiator and presented a systematic approach for assessing radiators.…”
Section: Introductionmentioning
confidence: 99%
“…Datas and Martí [ 10 ] reviewed the state of the art and historical development of TPV for space application along with the main competing technologies. Tain et al [ 11 ] reported the recent progress of near-field and far-field radiative heat transfer, various design structures of metamaterials and their properties, and focused on the exploration of tunable radiative wavelength selectivity of nano-metamaterials. More recently, in 2019, Sakakibara et al [ 12 ] reviewed the state of the art of radiator and presented a systematic approach for assessing radiators.…”
Section: Introductionmentioning
confidence: 99%
“…Within the last decade, nanostructured metamaterials have become an attractive topic in the field of radiative heat transfer for thermal energy harvesting ( Bello and Shanmugan, 2020 ; Jin et al., 2016 ; Khodasevych et al., 2015 ; Woolf et al., 2018 ; Xu et al., 2020 ) and radiative cooling ( Raman et al., 2014 ; Zhai et al., 2017 ). For harvesting solar energy to heat, spectrally selective absorbers with high solar absorption and low infrared emission are highly desired for efficient energy conversion, and many metamaterial selective solar absorbers have been designed and experimentally demonstrated recently based on multilayer ( Chirumamilla et al., 2016 , 2019 ; Dyachenko et al., 2016 ; Khoza et al., 2019 ; Thomas et al., 2017 ; Wang et al., 2018 ), periodic tungsten convex or concave gratings ( Jae Lee et al., 2014 ; Wang et al., 2015 ; Wang and Wang, 2013 ), nickel nanopyramids and tungsten nanowires (WNWs)/doughnuts ( Behera and Joseph, 2017 ; Li et al., 2015 ; Tian et al., 2018 ), and nanoporous or nanoparticle composite structures ( Lu et al., 2016 , 2017 ; Prasad et al., 2018 ). Due to their submicron feature sizes, advanced fabrication techniques such as electron-beam lithography and focused-ion beam were usually needed for fabricating these metamaterial structures ( Wang et al., 2015 ), which are expensive with low throughput prohibiting their large-area application.…”
Section: Introductionmentioning
confidence: 99%
“…Selective absorbers are commonly used in various fields due to their high absorptivity at specific wavelengths [ 39 ]. Spectrally selective filters can be used in various applications involving solar absorbers [ 40 ], sensors [ 41 ], passive cooling [ 21 , 42 ], and thermophotovoltaic devices [ 43 ].…”
Section: Introductionmentioning
confidence: 99%